Experimental investigation on the mechanical properties of carbon-glass-jute fiber reinforced epoxy hybrid composites. (2021) - Velu, S.; Joseph, J.K.; Sivakumar, M.; Bupesh Raja, V.K.; Palanikumar, K.; Lenin, N.
Abstract: Composite laminate widens its application area with numerous researches. Carbon fiber has an excellent mechanical property, making a good choice for applications where as its cost make the designer to search for hybrid alternative. Mechanical properties were investigated on Carbon/jute/glass fibers reinforced hybrid composites. The Carbon/jute/glass fiber hybrid composites were manufactured with four different layers of texture, which are ordered in different grouping utilizing the hand-layup procedure with weight proportion of fiber to matrix 40:60. Six distinctive plate were fabricated for investigation. The laminate was tested on Universal Testing Machine (UTM) and impact testing machine has been utilized to achieve this examination. By adding the carbon fiber, the strength of the composites was improved. In experimental study also reveals that carbon fiber has very excellent mechanical properties compare to glass fiber and jute fiber but it's too exorbitant and the grouping of fiber assumes an imperative job in strength of the overlay.